2008
DOI: 10.1016/j.brainres.2008.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants prevent ethanol-associated apoptosis in fetal rhombencephalic neurons

Abstract: It is well known that ethanol damages the developing nervous system by augmenting apoptosis. Previously, this laboratory reported that ethanol augments apoptosis in fetal rhombencephalic neurons, and that the increased apoptosis is associated with reduced activity of the phosphatidylinositol 3'kinase pathway and downstream expression of pro-survival genes. Other laboratories have shown that another mechanism by which ethanol induces apoptosis in developing neurons is through the generation of reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 52 publications
0
59
1
Order By: Relevance
“…Although it has been reported that the lipoic acid is an effective protecting antioxidant in the neuronal tissues [37], but it has been also observed that vitamin E prevents ethanol induced brain damages in developing rats potently [38]. Therefore, it seems that common property of the vitamin E and lipoic acid as natural antioxidants plays a crucial role in their protective effects against ethanol induced pathologic processes in the brain but the different patterns of changes in biochemical markers of oxidative stress, antioxidative defensive system and DNA damages reveal that an additional mechanisms besides oxidative stress are contributed to the observed changes and different molecular targets are being affected in the context of anti oxidative defensive system probably in a "tissuespecific" manner.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that the lipoic acid is an effective protecting antioxidant in the neuronal tissues [37], but it has been also observed that vitamin E prevents ethanol induced brain damages in developing rats potently [38]. Therefore, it seems that common property of the vitamin E and lipoic acid as natural antioxidants plays a crucial role in their protective effects against ethanol induced pathologic processes in the brain but the different patterns of changes in biochemical markers of oxidative stress, antioxidative defensive system and DNA damages reveal that an additional mechanisms besides oxidative stress are contributed to the observed changes and different molecular targets are being affected in the context of anti oxidative defensive system probably in a "tissuespecific" manner.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the strong therapeutic potential, clinical trials for resveratrol in human for various diseases are currently being conducted (http:// clinicaltrials.gov/ct2/results?termϭresveratrol). Prior studies have shown that resveratrol prevented ethanol-induced apoptosis in embryonic stem cells and ethanol-disrupted mouse blastocyst development (Huang et al, 2007) and also protected ethanol-induced apoptosis in fetal rhombencephalic neurons (Antonio and Druse, 2008). In a recent study, resveratrol was found to improve ethanol-induced cognitive deficits in a rodent model of FASD (Tiwari and Chopra, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…Since the development of the CNS is profoundly disturbed by exposure to ETH during the prenatal period (Heaton et al, 2003), it has been reported that its most harmful effects are caused by ROS, especially by some oxygen and other free radicals (Agar et al, 2003;Baydas and Tuzcu, 2005;Kozan et al, 2007;Montoliu et al, 1994;Nordmann et al, 1990;Nordmann et al, 1992). Recently, it has been suggested that apoptosis is involved, although the precise mechanism of ETH toxicity on the developing CNS is not elucidated so far (Antonio and Druse, 2008). In this experiment, our hypothesis was that MLT can act as a protective agent against ETH damaging in the developing PNS during the prenatal period, due to the fact that it is a potent free radical scavenger and antioxidant (Reiter, 1998;Reiter et al, 1994;Tan et al, 2000;Tunc et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that antioxidant/free radical scavenging properties of various antioxidants, e.g. MLT, have a putative role in their anti-apoptotic effects (Antonio and Druse, 2008). Reportedly, MLT prevents H2O2 activation of the pro-apoptotic enzyme, caspase-3 (Juknat et al, 2005).…”
Section: Discussionmentioning
confidence: 99%